2010
DOI: 10.1345/aph.1p172
|View full text |Cite
|
Sign up to set email alerts
|

Thoughts and Acts of Aggression/Violence Toward Others Reported in Association with Varenicline

Abstract: The clear temporal relationship, lack of prior history of this behavior, and unusual nature of these events strengthens the accumulating scientific evidence that varenicline is associated with thoughts and acts of aggression/violence. We recommend that physicians and pharmacists ensure that all patients are informed of possible psychiatric symptoms of varenicline, including violent and aggressive thoughts. All patients should be advised to contact a health-care provider immediately if these symptoms occur and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 2 publications
0
28
0
Order By: Relevance
“…Additionally, a recent study in smokers identified anxiety as one of the symptom domains in which varenicline treatment was ineffective (Cinciripini et al, 2013). Therefore, this lack of anxiolytic activity during nicotine withdrawal may underlie the low success rate of varenicline in a subset of smokers (Garrison and Dugan, 2009;Moore et al, 2010). Because varenicline acts at a number of different nAChR subtypes, identifying those subtypes that underlie the beneficial effects of the drug while avoiding subtypes responsible for negative side effects is necessary.…”
Section: Anxiolytic Effects and Nachr Regulation Of Abt-089 Discussionmentioning
confidence: 99%
“…Additionally, a recent study in smokers identified anxiety as one of the symptom domains in which varenicline treatment was ineffective (Cinciripini et al, 2013). Therefore, this lack of anxiolytic activity during nicotine withdrawal may underlie the low success rate of varenicline in a subset of smokers (Garrison and Dugan, 2009;Moore et al, 2010). Because varenicline acts at a number of different nAChR subtypes, identifying those subtypes that underlie the beneficial effects of the drug while avoiding subtypes responsible for negative side effects is necessary.…”
Section: Anxiolytic Effects and Nachr Regulation Of Abt-089 Discussionmentioning
confidence: 99%
“…The risk of additional serious adverse events associated with varenicline use includes the potential for serious neuropsychiatric symptoms such as depressed mood, agitation and suicidal thoughts. 32 These additional risks associated with varenicline have resulted in a boxed warning (the highest level of FDA warning) in the medication guide and a Risk Evaluation and Mitigation Strategy for varenicline in the United States. 32 All smoking cessation therapies are approved for short-term use.…”
Section: Overallmentioning
confidence: 99%
“…32 These additional risks associated with varenicline have resulted in a boxed warning (the highest level of FDA warning) in the medication guide and a Risk Evaluation and Mitigation Strategy for varenicline in the United States. 32 All smoking cessation therapies are approved for short-term use. Long-term efficacy and safety data are lacking for all currently approved therapies, including bupropion.…”
Section: Overallmentioning
confidence: 99%
“…A paper published on 20 July in The Annals of Pharmacotherapy highlighted 26 instances in which Chantix users became violent in thought or action 1 . In one case, a woman hit her 17-year-old daughter while the girl was driving a car.…”
mentioning
confidence: 99%
“…"The FDA has a little bit more power, but it has to develop the courage to use that power, " says Curt Furberg, a physician with the Division of Public Health Sciences at the Wake Forest University School of Medicine in Winston-Salem, North Carolina, and a co-author on the latest Chantix paper 1 . Furberg and others have expressed concern that the FDA's post-marketing watchdogs work under regulators who may be reluctant to question a drug's safety, having approved the drug in the first place.…”
mentioning
confidence: 99%